Ultraviolet protection factor evaluation of comfort oriented two-yarn fleece fabrics. (September 2022) - Sohaib Anas, Muhammad; Abbas, Adeel; Azam, Zeeshan; Tariq, Zeeshan; Gul, Zarnab; Sarwar, Muhammad Ehtisham
Knitted fleece fabrics with superior comfort characteristics are chiefly focused in winter wear. Thermal characteristics are an area of interest in selecting fleece clothing. However, environmental hazards also need to be focused. Fleece clothing is worn in cold areas having higher ultraviolet rays exposures. Hence the clothing should have the capability of combating environmental challenges. The study focuses on engineering variable fleece structures with different materials. Cotton, nylon, and polypropylene fleece patterns have been knitted using fleece 1:1, 3:1, and 2:2 patterns. The designs vary by tuck and miss stitch configurations in the fleece course. Comfort characteristics were determined through air permeability, moisture management, and thermal resistance tests. Performance criteria were evaluated in terms of pilling resistance and ultraviolet protection factor (UPF) investigation. Structures and materials owing better comfort characteristics with satisfactory UPF have been predicted as safe clothing in UV affected zones, that is, fleece 3:1 possessed the optimum comfort characteristics and UPF simultaneously; however, the mechanical performance was better for 2:1 and 1:1 fleece fabric due to less amount of miss stitch floating yarns.